Aggressive behavior in cats exposed to trauma - YAYLA, Sadık; ALTAN, Semih; ersöz kanay, berna; çatalkaya, emine; saylak, nahit (Journal of the Hellenic Veterinary Medical Society, 2022)
Aggression is an important behavioral problem in cats. This issue can occur as a reaction when there is disease or pain in a normal cat. The aim of this study is to evaluate the behavior changes of cats exposed to trauma using behavior scoring system and demeanour scoring system. In this study consisted of 135 cats of different breeds, ages and genders with high rise syndrome and traffic accidents. These cats were given a detailed clinical and radiological examination. Demeanour scoring system, behavior tests, and visual analog scale were used to identify behavior changes and pain in cats. The findings from this study showed that cats exposed to trauma may experience behavioral changes or agression, and this may result from pain or stress from trauma. As a result, stress from trauma in cats can also lead to a change in behavior, a temporary aggressiveness.